THE LEGAL CONSEQUENCES OF DRAFTING A POWER OF ATTORNEY FOR THE SALE OF LAND WITHOUT THE CONSENT OF THE OWNER OR RIGHTS HOLDER OF THE LAND: (Case Study of Decision Number 1615K/PDT/2020) - Chandra, Yulius; Gunadi, Ariawan (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The Public Notary (PPAT) in carrying out their duties and responsibilities, especially in creating authentic deeds, can result in errors, both in terms of formal requirements and material requirements. The issue involves sanctioning notaries involved in illegal activities related to power of attorney deeds in land transactions without the owner's consent, as discussed in Decision Number 1615 K/PDT/2020. The research method used in this study is normative juridical research based on secondary data. The research results show that in order to protect the community from notarial actions that may harm the public, there are five types of sanctions: oral reprimand, written reprimand, temporary suspension, honorable dismissal, or dishonorable dismissal. Sanctions in the form of written warnings and reprimands can only be imposed by the Regional Supervisory Council. Sanctions in the form of temporary suspension from the position of notary can only be carried out by the Central Supervisory Council, and sanctions in the form of honorable or dishonorable dismissal from the position of notary can only be carried out by the Minister upon the recommendation of the Central Supervisory Council. The legal consequence of creating power of attorney deeds in land transactions without the knowledge of the owner or the land rights holder, as stated in Decision Number 1615 K/PDT/2020, is a legally flawed and invalid process, as it does not meet the requirements set at the time of its creation. PPAT, in carrying out their duties, especially in creating deeds, should be guided by honesty, independence, impartiality, and accountability.